2011
DOI: 10.1111/j.1439-0531.2011.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentially Expressed Genes in Ovaries of Polytocous versus Monotocous Dairy Goats Using Suppressive Subtractive Hybridization

Abstract: In this study, suppressive subtractive hybridization (SSH) was performed to screen differentially expressed genes in ovarian tissues between polytocous and monotocous goats. From the SSH cDNA library, we obtained 29 differentially expressed sequence tags (ESTs) that have high similarity with known genes in the public database, which were involved in signal transduction, transcriptional regulation, cellular molecular dynamics, cytoskeleton, metabolism and oxidation-reduction. In addition, one novel EST that has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…In a previous study, we have demonstrated that Timp1, a differentially expressed gene, was screened from ovarian tissues between polytocous and monotocous Guanzhong dairy goats by suppressive subtractive hybridization [23]. The results confirmed that the different levels of Timp1 mRNA expression in the ovarian tissues of polytocous and monotocous goats could lead to different ovulation rates, which causes a difference in litter size.…”
Section: Introductionsupporting
confidence: 87%
“…In a previous study, we have demonstrated that Timp1, a differentially expressed gene, was screened from ovarian tissues between polytocous and monotocous Guanzhong dairy goats by suppressive subtractive hybridization [23]. The results confirmed that the different levels of Timp1 mRNA expression in the ovarian tissues of polytocous and monotocous goats could lead to different ovulation rates, which causes a difference in litter size.…”
Section: Introductionsupporting
confidence: 87%
“…These results indicate that litter size is a complicated trait. The number of differentially upregulated genes identified herein (>1000) was substantially more than previous reports from An et al (2012) (29 differentially up-regulated genes) or Chen et al (2012) (114 differentially up-regulated genes); this could be due to the tissues chosen for analysis, as the previous work was limited to the ovary whereas we looked at tissue representing the entire HPG axis.…”
Section: Discussionmentioning
confidence: 60%
“…Three genes identified by our SSH experiment had been previously identified by An et al (2012): ornithine decarboxylase antizyme 1 (OAZ1); ATP synthase, Hþ transporting, mitochondrial F1 complex, alpha subunit 1 (ATP5A1); and ribosomal protein L5 (RPL5). OAZ1 was identified in the hypothalamus and ovary (1 time each) of sexually mature Jining Grey goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study suggested that increased OAZ1 expression might disrupt polyamine homeostasis by inhibiting ODC activity and suppress follicular development in geese [21]. Recently, studies from our and others laboratories indicate that OAZ1 regulates the ovarian and follicular development and ovulation by mediating intracellular polyamine homeostasis in the ovary [2123]. Granulosa cells play a critical role in ovarian functions such as follicular development, ovulation, and steroidogenesis in both mammals and birds.…”
Section: Introductionmentioning
confidence: 99%